Usability of Immunohistochemistry in Forensic Samples With Varying Decomposition. (September 2018) - Lesnikova, Iana; Schreckenbach, Marc Niclas; Kristensen, Maria Pihlmann; Papanikolaou, Liv Lindegaard; Hamilton-Dutoit, Stephen
Abstract : Abstract: Immunohistochemistry (IHC) is an important diagnostic tool in anatomic and surgical pathology but is used less frequently in forensic pathology. Degradation of tissue because of postmortem decomposition is believed to be a major limiting factor, although it is unclear what impact such degradation actually has on IHC staining validity. This study included 120 forensic autopsy samples of liver, lung, and brain tissues obtained for diagnostic purposes. The time from death to autopsy ranged between 1 and more than 14 days. Samples were prepared using the tissue microarray technique. The antibodies chosen for the study included KL1 (for staining bile duct epithelium), S100 (for staining glial cells and myelin), vimentin (for endothelial cells in cerebral blood vessels), and CD45 (for pulmonary lymphocytes). Slides were evaluated by light microscopy. Immunohistochemistry reactions were scored according to a system based on the extent and intensity of the positive stain. An overall correlation between the postmortem interval and the IHC score for all tissue samples was found. Samples from decedents with a postmortem interval of 1 to 3 days showed positive staining with all antibodies, whereas samples from decedents with a longer postmortem interval showed decreased staining rates. Our results suggest that IHC analysis can be successfully used for postmortem diagnosis in a range of autopsy samples showing lesser degrees of decomposition.